2006
DOI: 10.1124/mol.106.027847
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Peloruside A and Laulimalide with Taxoid Site Drugs, but Not with Each Other, on Tubulin Assembly

Abstract: Previous studies on the drug content of pelleted tubulin polymers suggest that peloruside A binds in the laulimalide site, which is distinct from the taxoid site. In a tubulin assembly system containing microtubule-associated proteins and GTP, however, peloruside A was significantly less active than laulimalide, inducing assembly in a manner that was most similar to sarcodictyins A and B. Because peloruside A thus far seems to be the only compound that mimics the action of laulimalide, we examined combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 37 publications
7
114
0
Order By: Relevance
“…4,5 It is also active in multidrug-resistant cancer cell lines overexpressing P-glycoprotein (P-gp) and is both effective in taxoid-resistant cell lines 5 and synergistic with taxoids. 6 These findings suggest that laulimalide may form the basis for a next-generation antimitotic agent, although we note lingering concerns over toxicity. 7 MT stabilizers interfere with MT dynamics and alter mitotic processes.…”
Section: Introductionmentioning
confidence: 85%
“…4,5 It is also active in multidrug-resistant cancer cell lines overexpressing P-glycoprotein (P-gp) and is both effective in taxoid-resistant cell lines 5 and synergistic with taxoids. 6 These findings suggest that laulimalide may form the basis for a next-generation antimitotic agent, although we note lingering concerns over toxicity. 7 MT stabilizers interfere with MT dynamics and alter mitotic processes.…”
Section: Introductionmentioning
confidence: 85%
“…This is known from studies that indicate synergy between peloruside A or laulimalide and other microtubulestabilizing drugs, all of which bind at the paclitaxel binding site, [9][10][11]23 as well as from direct binding studies that have shown that microtubules formed in vitro and taxol-saturated can still bind peloruside A and vice-versa. 8,21 These results demonstrated that the binding site for peloruside A and laulimalide was a new drug site on tubulin, but did not indicate where on tubulin it might be.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…It has the advantage of being less lipophilic than paclitaxel and binds to a-tubulin on the laulimalide-binding site (52). This binding site distinct from the taxanes raises the possibility of combining drugs that act on laulimalide and taxane-binding sites-a synergistic antiproliferative effect has already been seen in vitro (53).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%